Combined seed enhancement technique involving seed priming and coating for improvised anatomical potential and vigour of okra seeds (Abelmoschus esculentus L.) - L, Anilkumar; K, Malarkodi (Journal of Phytology, 2019)
The study was conducted to standardize the methodology of humid priming for improving the seed germination and vigour of okra seeds and to compare the efficacy of different enhancement techniques such as hydro priming, spin priming, seed coating and the combination of ‘humid priming + seed coating’ in improving the seed vigour characteristics of okra (Abelmoschus esculentus L.). In order to standardize the humid priming technique, okra seeds were subjected to humid priming for four different duration’s viz., 2, 4, 6 and 8 h, shade dried to original moisture content and subjected to evaluation of seed germination under shade net conditions in raised beds. The results revealed that 4 h of humid priming was statistically significant to the rest of the durations, with respect seed germination and seedling growth. With respect to anatomical potential, the radicle length (3.39mm), cotyledon length (6.69mm) and cotyledon width (6.30mm), recorded by humid priming (4 h) was 62.2 %, 6.4 % and 2.6 % higher than control seeds. The second experiment conducted to compare the efficacy of hydro priming, spin priming, polymer coating and combination of humid priming + seed coating. The study revealed that seeds subjected to combination of humid priming (4 h) + seed coating (3g kg-1) recorded highest physiological potential in terms of germination percentage (87 %), seedling length (20.2 cm), dry matter production (421.3 mg), vigour index (1765), root volume (3.5 cm3) and root sheath (2.560 g) while the control recorded only 70 %, 15.1 cm, 328.7 mg, 1055, 2.0 cm3 and 1.532 g, respectively.